Evaluation of Australian soup manufacturer compliance with national sodium reduction targets. Issue 2 (30th October 2017) - Levi, Rebecca; Probst, Yasmine; Crino, Michelle; Dunford, Elizabeth
Abstract : Aim: Packaged foods dominate Australia's food supply and are important contributors to nutrition‐related disease. To help address this problem, the Food and Health Dialogue (FHD) was launched in 2009, setting voluntary sodium reduction targets for various categories of packaged foods. The aim of this study was to examine the food industry's progress and compliance with the FHD sodium reduction targets for soup products. Methods: Nutritional information was collected from product labels of all soup products available from four major Australian supermarkets annually between 2011 and 2014. Products were assigned to categories in line with those in the FHD. The proportion of soup products meeting sodium reduction targets was examined by (i) soup category; (ii) FHD participant status; and (iii) manufacturer. Results: A 6% reduction in sodium levels in soups overall was found from 2011 to 2014 ( P  = 0.002). Significant reductions were observed for FHD participants ( P  < 0.05 for all) but not for non‐participants. In 2014, 67% dry soups and 76% of wet soups met national sodium reduction targets. Conclusions: Despite the majority of soup products meeting the sodium reduction targets specified by the FHD, re‐evaluation of the targets may be required to further reduce sodium levels in soups. Manufacturers participating in the FHD are likely to be driving sodium reductions in the Australian soup market, further highlighting the need for continued government leadership in this area to ensure all manufacturers are actively involved in the process.